Effect of Hydrothermal Extraction Condition on The Content of Phenolic Compound Extracted from Rind of Mangosteen (Garcinia mangostana) and Its Antioxidant Efficiency - Ash Shiddiqi, Qifni Yasa; Karisma, Achmad Dwitama; Machmudah, Siti; Widiyastuti, Widiyastuti; Nurtono, Tantular; Winardi, Sugeng; Wahyudiono, Wahyudiono; Goto, Motonobu (IPTEK The Journal for Technology and Science, 2014)
Xanthone is an antioxidant compound contained in the rind of mangosteen. There are some methods to extract Xanthone from rind of mangosteen, and one of them is hydrothermal extraction. Hydrothermal extraction is a method to obtain xanthone from rind of mangosteen using water at teIn this work, the effect of extraction temperature, pressure, and mode (batch and continuous), and particle size of starting material on the yield and recovery of extracted xanthone and phenolic compounds was investigated. Extraction was carried out at various temperatures (120, 150, and 180oC) and pressures (1, 3, and 5 MPa) and constant flow rate of 1 mL/min. The xanthone content and antioxidant efficiency of extract was examined by using spectrophotometer, while the concentration of total phenolic compounds in the extract was determined with folin ciocalteu reagent and examined using spectrophotometer In order to confirm the extracted phenolic compounds, the extract residue was analyzed by using FTIR. The experimental result showed that the increase in pressure and temperature caused an increase in total phenolic compound concentration and yield of xanthone. In addition, the result also showed that antioxidant activities were observed in the extract of mangosteen rind.